Epoxy-Compositions filled by Nanosilicaand water-binder Mineral Fillers, for Out-Clinical Dental Self-Treatment and Profilaxis of Carious or Traumatic Dental Damages - Starokadomsky, D.; Reshetnyk, M. (Jour Med Resh and Health Sci, 2023)
The highly filled epoxy-mineral compositions capable to polymerize in wet or water conditions, were investigated. Their ?ompositions consist of ordinary, cheap, commonly available components, and are filled with water-curing fillers (gypsum, cement). The technology of their curing provides for a combination of exposure and heating modes before application. They water-cured epoxy-compositions can be use for fast dental filling and restoring damages of teeth, outside of clinical conditions. These hypotheses found confirmation in the obtained results of dental repair on volunteers. The tooth powders and epoxy-composites from cheap available components, for use by non-specialists in domestic and non-clinical conditions – were developed and proposed. These compositions (subject to the filling technology) turn into strong polymer linings or coatings, with a high percentage of formation of functional and durable fillings in patients with dental disorders. These results will be very useful for people and communities who, for various reasons (wars, out-cities, voyages, poverty, workload), are left without access to quality dental services or clinics.